The Hidden Work of Challenging Precarity - Mirchandani, Kiran; Hande, Mary Jean (Canadian Journal of Sociology, 2020)
This article explores the hidden work of workers employed in precarious jobs which are characterized by part-time and temporary contracts, limited control over work schedules, and poor access to regulatory protection. Through 77 semi-structured interviews with workers in low-wage, precarious jobs in Ontario, Canada, we examine workers’ attempts to challenge the precarity they face when confronted by workplace conditions violating the Ontario Employment Standards Act (ESA), such as not being paid minimum wages, not being paid for overtime, being fired wrongfully or being subject to reprisals. We argue that these challenges involve hidden work, which is neither acknowledged nor recognized in the current ESA enforcement regime. We examine three types of hidden work that involve (1) creating a sense of positive self-worth amidst disempowering practices; (2) engaging in advocacy vis-à-vis employers, sometimes through launching official claims with the Ontario Ministry of Labour; and (3) developing strategies to avoid the costs of precarity in the future. We argue that this hidden work of challenging precarity needs to be formally recognized and that concrete strategies for doing so might lead to more robust protection for workers, particularly within ESA enforcement practices.
Keywords: Canada